Public Reception of Legal Processes Involving Public Figures: A Sociological and Religious Perspective on Public Morality and Legal Institutions - Sumarta Sumarta; Rosidin; Kusyana; Dinata Firmansyah (Lentera Peradaban: Journal on Islamic Studies, 2025)
This study examines social acceptance of legal processes involving public figures or state officials, focusing on the interplay between public perception, religious values, and prevailing social norms. The background problem lies in the increasing number of legal cases involving public figures in Indonesia and the diverse societal responses to these proceedings. Utilizing a qualitative approach through case studies and in-depth interviews, the research explores how public opinion is shaped by moral values and trust in legal institutions. The findings reveal that social acceptance of legal processes is significantly influenced by religious values, socio-political proximity to the figure involved, and the credibility of the legal institutions managing the case. In some instances, religious norms are used either to justify or reject ongoing legal processes. The study concludes that achieving public-perceived justice requires legal institutions to strengthen public trust and consider the sensitivity of prevailing social and religious values within the community.